2011
DOI: 10.1073/pnas.1010122108
|View full text |Cite
|
Sign up to set email alerts
|

Deep bradycardia and heart block caused by inducible cardiac-specific knockout of the pacemaker channel gene Hcn4

Abstract: Cardiac pacemaking generation and modulation rely on the coordinated activity of several processes. Although a wealth of evidence indicates a relevant role of the I f ("funny," or pacemaker) current, whose molecular constituents are the hyperpolarization-activated, cyclic nucleotide-gated (HCN) channels and particularly HCN4, work with mice where Hcn genes were knocked out, or functionally modified, has challenged this view. However, no previous studies used a cardiac-specific promoter to induce HCN4 ablation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
232
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(251 citation statements)
references
References 27 publications
(61 reference statements)
13
232
1
3
Order By: Relevance
“…Several ion channels also directly bind cyclic nucleotides, which modulates the activation characteristics or gating properties of these channels; therefore, cAMP regulates membrane potential and excitability of cells. Although HCN4 plays an important role in cardiac pacemaker function (51,52), despite its ability to directly bind cAMP, its role in stress adaptation of the cardiac pacemaker remains a matter of debate (51,(53)(54)(55). Therefore, our present identification of Popdc proteins as a class of membrane-localized cAMP binding proteins in sinus node cells and our finding that genetic loss resulted in stress-induced bradycardia suggest that Popdc proteins are part of the molecular network involved in cardiac pacemaker regulation in response to adrenergic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several ion channels also directly bind cyclic nucleotides, which modulates the activation characteristics or gating properties of these channels; therefore, cAMP regulates membrane potential and excitability of cells. Although HCN4 plays an important role in cardiac pacemaker function (51,52), despite its ability to directly bind cAMP, its role in stress adaptation of the cardiac pacemaker remains a matter of debate (51,(53)(54)(55). Therefore, our present identification of Popdc proteins as a class of membrane-localized cAMP binding proteins in sinus node cells and our finding that genetic loss resulted in stress-induced bradycardia suggest that Popdc proteins are part of the molecular network involved in cardiac pacemaker regulation in response to adrenergic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Here, we have shown that CD166-expressing cells also express HCN4 (Figure 1), a protein that specifically delineates the SAN region during embryogenesis 14,15,41 and in adulthood. [42][43][44][45] HCN4 is also fundamental for sinus node function because its absence is incompatible with life 29,30 and mutations in its sequence can cause inherited rhythm disturbances. 46 Here, we show that freshly selected CD166 + cells, but not CD166 − cells, express high levels of HCN4 mRNA; at 1 day after sorting, most of the cells express the HCN4 proteins (Online Figure IV).…”
Section: Discussionmentioning
confidence: 99%
“…Because HCN channels are critical for pacemaker activity in both embryonic and adult SAN, 29,30 and because their ectopic expression induces repetitive spontaneous activity in the ventricle, 31 we evaluated the expression of various HCN subunits at the protein level after 1 or 3 weeks in culture ( Figure 5). In agreement with qRT-PCR data, we found that after 1 week in culture, CD166 + cells expressed both HCN1 ( Figure 5B) and HCN4 ( Figure 5E) together with the cardiac markers α-actinin (α-act; Figure 5A and 5D), whereas HCN2, the main ventricular isoform, 32 could not be detected in α-act-positive cells ( Figure 5G and 5H).…”
Section: Hcn and Calcium Channels Are Functional In Cd166-selected Camentioning
confidence: 99%
“…49 In some nonconstitutive knockout models, only mild effects on cardiac automaticity were observed with no alterations of HR control. 50,51 Ablation of HCN4 in an inducible and cardiac-specific HCN4 knockout mouse model 52 led to progressive development of severe bradycardia (≈50% reduction of the original HR) and atrioventricular block, accompanied by cardiac arrest and death. In vitro analysis of SAN myocytes isolated from these mice revealed strong reductions of both the I f current (by ≈70%) and spontaneous HR generation (by ≈60%).…”
Section: Hcn Function and Diseasementioning
confidence: 99%